2023
DOI: 10.3390/ijms241210367
|View full text |Cite
|
Sign up to set email alerts
|

UV-C Seed Surface Sterilization and Fe, Zn, Mg, Cr Biofortification of Wheat Sprouts as an Effective Strategy of Bioelement Supplementation

Katarzyna Czarnek,
Małgorzata Tatarczak-Michalewska,
Piotr Dreher
et al.

Abstract: Metalloenzymes play an important role in the regulation of many biological functions. An effective way to prevent deficiencies of essential minerals in human diets is the biofortification of plant materials. The process of enriching crop sprouts under hydroponic conditions is the easiest and cheapest to conduct and control. In this study, the sprouts of the wheat (Triticum aestivum L.) varieties Arkadia and Tonacja underwent biofortification with Fe, Zn, Mg, and Cr solutions in hydroponic media at four concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Finally, other methods based on physical principles have been implemented for seed treatment: irradiation by UV-C light has been used as a way to sterilize seed surface [153] and there is evidence that some seed-transmitted fungi may be killed by an appropriate UV-C treatment [154]. Regretfully, UV-C irradiation does not have a significant direct effect on seed endophytes, particularly bacteria, despite some authors reporting that a UV-C treatment was able to induce a resistant state in cabbage against Xanthomonas campestris pv.…”
Section: Uv-c Light Irradiationmentioning
confidence: 99%
“…Finally, other methods based on physical principles have been implemented for seed treatment: irradiation by UV-C light has been used as a way to sterilize seed surface [153] and there is evidence that some seed-transmitted fungi may be killed by an appropriate UV-C treatment [154]. Regretfully, UV-C irradiation does not have a significant direct effect on seed endophytes, particularly bacteria, despite some authors reporting that a UV-C treatment was able to induce a resistant state in cabbage against Xanthomonas campestris pv.…”
Section: Uv-c Light Irradiationmentioning
confidence: 99%
“…Finally, other methods based on physical principles have been implemented for seed treatment: irradiation by UV-C light has been used as a way to sterilise seed surface [173] and there is evidence that some seed-transmitted fungi may be killed by an appropriate UV-C treatment [174,175]. Regretfully, UV-C irradiation does not have a significant, direct effect on seed endophytes, particularly bacteria, despite some authors reported that an UV-C treatment was able to induce a resistant state in cabbage against Xanthomonas campestris pv.…”
Section: Uv-c Light Irradiationmentioning
confidence: 99%